2023
DOI: 10.1101/2023.08.11.553014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Electron Transport Chain ofShewanella oneidensisMR-1 can Operate Bidirectionally to Enable Microbial Electrosynthesis

Abstract: Extracellular electron transfer (EET) is a process by which bacterial cells can exchange electrons with a redox active material located outside of the cell. InShewanella oneidensis, this process is natively used to facilitate respiration using extracellular electron acceptors such as Fe(III) or an anode. Previously, it was demonstrated that this process can be used to drive microbial electrosynthesis of 2,3-butanediol (2,3-BDO) inS. oneidensisexogenously expressing butanediol dehydrogenase (Bdh). Electrons tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…9 Past work with S. oneidensis is also consistent with IMF-dependent EEU to the cytoplasm. 25,29,67,83,84 Tefft and TerAvest (2019) reported EEU in S. oneidensis + Bdh + PR (proteorhodopsin), where PR, a light-driven proton pump, provided PMF. 67 On a cathode, S. oneidensis + Bdh + PR, rapidly responded to changes in light, indicating that EEU might be PMF-limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Past work with S. oneidensis is also consistent with IMF-dependent EEU to the cytoplasm. 25,29,67,83,84 Tefft and TerAvest (2019) reported EEU in S. oneidensis + Bdh + PR (proteorhodopsin), where PR, a light-driven proton pump, provided PMF. 67 On a cathode, S. oneidensis + Bdh + PR, rapidly responded to changes in light, indicating that EEU might be PMF-limited.…”
Section: Discussionmentioning
confidence: 99%
“…83,84 Ford and TerAvest (2023) demonstrated that PMF from terminal oxidases was also su cient to drive EEU to the cytoplasm in place of PR in S. oneidensis + Bdh. 29 Tefft et al (2022) found that CCCP interfered with EEU to the cytoplasm, but not to fumarate reductase (FccA) in the periplasm. 25 As illustrated by Ross et al (2011), 85% of EEU to FccA must go through the quinone pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation